Customer Satisfaction at Babeh Sadeli Typical Betawi Restaurant - Anita Swantari; Filma Festivalia; Haryo Wicaksono; Mimi Enggriani (At-Tadbir : jurnal ilmiah manajemen, 2023)
This study aims to determine the effect of service quality and facilities on customer satisfaction at Babeh Sadeli Typical Betawi Restaurant. This type of research is descriptive research with a quantitative approach with a simple regression analysis method which is processed with the help of the SPSS program. The population in this study were all visitors who had come to the Betawi Babeh Sadeli Restaurant. At the same time, the sample in this study amounted to 100 respondents. Data collection techniques by distributing questionnaires. The sampling technique used is accidental sampling. The results showed that the quality of service and facilities significantly affected the variable of customer satisfaction. Customer satisfaction. This indicates that the Betawi Babeh Sadeli Restaurant provides quality consisting of security, security, and supervision.